DYNAMIC DIPLOMACY: A STUDY OF THE COMMUNIST INTERNATIONAL'S POLICY CHANGES AND THEIR IMPACT (1923-1925) - adminAndrzej, Kowalski Jan; Oliver, Samuel (International Journal of Political Science and International Relations (IJPSIR), 2024)
The aftermath of World War I ignited the Bolsheviks' optimism that the flames of revolution would soon engulf other nations across Europe. The Communist International, established in March 1919 under the guidance of Vladimir Lenin, emerged as the epicenter of the global communist movement and a potent instrument to further this revolutionary agenda. While the Communist International's primary mission was to propagate communism and galvanize the working class in their struggle for labor rights, it also undertook more clandestine roles. Between the early post-war years and 1923, the organization maintained close collaboration with both military and political intelligence apparatuses of the Soviet state. Formally established in 1921 by a resolution passed during the Communist International Congress, the International Liaison Department (later known as OMS, or Otdel Mezhdunarodnykh Svyazi) played a pivotal role in these covert operations. Its mandate encompassed the provision of support, leadership, and financing to communist parties worldwide. This assistance extended beyond financial aid, encompassing the supply of weaponry, personnel, and technical expertise. In essence, the OMS functioned as the nerve center for intelligence activities conducted by communist parties on a global scale, acting as a convergence point for both civilian and military intelligence operations Within the Communist International, the OMS harnessed the resources of local communist structures to gather intelligence for the Soviet state, which served as the progenitor of the international communist movement. In addition to the committed communists who consciously undertook intelligence assignments during this era, the OMS also relied on unwitting local communists to subvert their own governments. This intricate web of intelligence activities and subterfuge shaped the landscape of international communism during the interwar period.